Prototipe Modul Praktik untuk Pengembangan Aplikasi Internet of Things (IoT) - Agus Wagyana (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2019)
Internet of things is one of the pillars of Industry 4.0 so that the competence of concepts and practices is very useful, especially for students or workers. This practice module is designed to support practical activities (or training) for developing Internet of Things applications. The method used to make the prototype of this module consists of determining specifications, designing and selecting appropriate hardware, application development, and testing. As a result, this module uses the ESP32 board as the main controller and a number of input and output components, which consist of ten different input components and seven different output components. In general, this prototype has worked well in accordance with specified specifications so that it can be used to develop various IoT applications with existing or added input and output components.